2010
DOI: 10.1073/pnas.1013305107
|View full text |Cite
|
Sign up to set email alerts
|

Neural basis of the undermining effect of monetary reward on intrinsic motivation

Abstract: Contrary to the widespread belief that people are positively motivated by reward incentives, some studies have shown that performance-based extrinsic reward can actually undermine a person's intrinsic motivation to engage in a task. This "undermining effect" has timely practical implications, given the burgeoning of performance-based incentive systems in contemporary society. It also presents a theoretical challenge for economic and reinforcement learning theories, which tend to assume that monetary incentives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
262
4
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(309 citation statements)
references
References 38 publications
31
262
4
2
Order By: Relevance
“…However, the undermining effects of extrinsic reinforcement on intrinsic motivation have been well known to social psychologists for decades: After receiving external inducements to engage in an enjoyable behavior, the frequency of that behavior decreases in the absence of the inducement (32,33). Recent data suggest that such "undermining" of intrinsic value is reflected in decreased en- gagement of reward-related neural structures (34). We suspect that the presence of external motivation (punishment threats) may diminish the intrinsic value otherwise associated with equitable choices; indeed, in some cases, sanctions reduce, rather than increase, prosocial behavior (35).…”
Section: Discussionmentioning
confidence: 99%
“…However, the undermining effects of extrinsic reinforcement on intrinsic motivation have been well known to social psychologists for decades: After receiving external inducements to engage in an enjoyable behavior, the frequency of that behavior decreases in the absence of the inducement (32,33). Recent data suggest that such "undermining" of intrinsic value is reflected in decreased en- gagement of reward-related neural structures (34). We suspect that the presence of external motivation (punishment threats) may diminish the intrinsic value otherwise associated with equitable choices; indeed, in some cases, sanctions reduce, rather than increase, prosocial behavior (35).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Murayama and colleagues demonstrated the undermining effect of reward on subsequent free choice behavior and neural activation, finding more limited engagement in the task and reduced activation in the anterior striatum, midbrain, and lateral prefrontal cortex following reward (Murayama, Matsumoto, Izuma, & Matsumoto, 2010). Thus, if outcomes beyond task performance are considered, all "rewards" (and sources of enhanced expectations) may not be equal.…”
Section: Mechanisms For Autonomy-support Effectsmentioning
confidence: 99%
“…The robustness of this effect has been generally accepted [but is still the subject of debate (6,8,9)]; indeed, recent research has found a possible neural basis for the "undermining effect" of instrumental rewards on internal motivation (10).…”
Section: Significancementioning
confidence: 99%